(untitled) (ENTHYMEMA, 2020)
This paper presents the results of a transdisciplinary research conducted by scholars working in the humanities and experimental psychologists in order to find an interface between the needs of a qualitative approach (mainly based on the evaluation of stylistic features) and those of a quantitative analysis, in order to find useful features for testing different reading behaviors and for new hermeneutical enquiries. The results of our research, which was conducted in two Labs (Dahlem Institute for Neuroimaging of Emotion at the FU Berlin and the NewHums – Neurocognitive and Human Studies at the University of Catania), consistently differ from previous ones, as they focus on the whole multi-layered foregrounded texture of a poem and try to evaluate predictable differences in reading, re-reading behaviour and meaning-making processes. We present the FAM, targeting foregrounding elements in three main categories: the phonological, morpho-syntactic, and rhetoric. To identify those elements, four different text levels were taken into account, the sublexical level of phonemes and syllables, the lexical level of single words, the interlexical level of word combinations across longer distance (e.g. two lines), and the supralexical level of whole stanzas or an entire poem. In contrast to previous quantitative analyses on short, isolated sentences and texts, mostly expository in nature (‘textoids’), or on single words or segments, the text is considered as a whole, marked by density fields that work as milestones along a reading route.